Dry bonding to dentin: Broadening the moisture spectrum and increasing wettability of etch-and-rinse adhesives - Stape Thiago Henrique Scarabello; Uctasli Merve; Cibelik Hatice Sümeyye; Tjäderhane Leo; Tezvergil-Mutluay Arzu (Elsevier Inc., 2022)
Objective
To determine whether the effect of dentin moisture on the etch-and-rinse bonding may be minimized by dry-bonding protocols utilizing aqueous or ethanolic dimethyl sulfoxide (DMSO) pretreatments.
Methods
H3PO4-etched mid-coronal dentin surfaces from human molars were randomly blot- or air-dried for 30 s and pretreated with DMSO/H2O or DMSO/EtOH solutions. Untreated samples served as control. Moisture control was performed by either blot- or air-drying. Samples were bonded with a multistep etch-and-rinse adhesive. Restored crown segments (n = 8/group) were stored in distilled water for 24 h and sectioned for microtensile bond strength testing. Resin-dentin beams (0.8 mm2) were tested under tension until fracture (0.5 mm/min) after 24 h and two years of storage in artificial saliva at 37 °C.
SEM nanoleakage evaluation was performed on aged samples. Collagen wettability was also measured by sessile drops of the hydrophilic and hydrophobic bonding resins (n = 8/group). Data were examined by factorial ANOVA followed by the Tukey test (α = 0.05).
Results
Dry bonding to untreated collagen produced inferior immediate and long-term bond strengths than wet bonding (p < 0.05). Regardless of initial hydration and moisture control, DMSO-dry bonding produced initially higher and stable bond strengths after aging (p < 0.05). DMSO-pretreated groups presented improved collagen wettability with lower silver uptake (p < 0.05).
Significance
Despite the common belief that etch-and-rinse adhesives must be applied onto moist collagen, DMSO-dry bonding protocols not only improved bonding performance and hybrid layer integrity, but also brought more versatility to collagen hybridization by reducing overdrying-related issues.